68Ga–Prostate-Specific Membrane Antigen PET/CT Findings in Extra-axial Metastasis From Prostate Carcinoma. (February 2020) - Kulkarni, Mukta; Vare, Ajay; Shetkar, Shubhangi; Surkar, Prashant; Joshi, Prathamesh; Kumar, Kritik
Abstract : Abstract: A 67-year-old man with no previous history of malignancy presented with trigeminal neuralgia. MRI of the brain revealed extra-axial lesion along right trigeminal nerve suggestive of neuroma. On histopathology, the lesion was found to be metastasis from adenocarcinoma prostate. Patient underwent 68 Ga–prostate-specific membrane antigen PET/CT for assessing the whole-body status of the disease, which revealed primary prostate lesion, metastatic bone lesions, and extra-axial lesion along the right trigeminal nerve. Extra-axial, intracranial metastasis from prostate carcinoma is an uncommon phenomenon. We describe 68 Ga–prostate-specific membrane antigen PET/CT findings in an exceedingly rare case of extra-axial metastatic lesion from prostate carcinoma.